What do we know about the Aztecs? - Defrates, Joanna (New York : P. Bedrick Books, 1992)
An illustrated introduction to the history, religion, customs, and eventual fate of the Aztecs.
Includes index.
Keywords: Aztecs -- Juvenile literature; Aztecs; Indians of Mexico